Method for manufacturing lithium metal electrode and lithium metal secondary battery
By forming a LiF protective layer on the surface of the lithium metal electrode, the problem of lithium dendrites forming during charging and discharging of lithium metal secondary batteries is solved, which improves the stability and life characteristics of the battery and reduces the safety risks in the process.
Patent Information
- Application Number
- CN202180005923.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-06-15
- Filing Date
- 2021-06-15
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2041-06-15
AI Technical Summary
Lithium metal secondary batteries are prone to form lithium dendrites during charging and discharging, resulting in deterioration of battery life characteristics and stability, and existing lubricants have problems of high flammability and harm to the human body.
Using a lubricant composition containing a fluorine solvent and a fluorine compound, the lithium metal reacts with a fluorine atom to form a LiF protective layer through a rolling process to inhibit the formation of dendrites.
It effectively suppresses the side reaction between lithium metal and electrolyte, improves the stability and life characteristics of lithium metal electrodes, and reduces safety risks in the process.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] This application claims priority to Korean Patent Application No. 10-2020-0072106, filed on Jun. 15, 2020, the disclosure of which is incorporated herein by reference.
[0002] The present invention relates to a method for manufacturing a lithium metal electrode and a lithium metal secondary battery, wherein the lithium metal secondary battery comprises the electrode manufactured by the above manufacturing method. Background Art
[0003] A lithium secondary battery is generally composed of a positive electrode, a negative electrode, a separator disposed therebetween, and an electrolyte. Recently, as the demand for high-capacity secondary batteries increases, lithium metal secondary batteries using active material lithium metal itself as a negative electrode capable of obtaining high energy density have been developed.
[0004] Lithium metal secondary batteries are secondary batteries that use lithium metal or lithium alloy as the negative electrode, wherein the lithium metal secondary batteries include, for example, lithium-metal oxide batteries, lithium-sulfur batteries, or lithium-air batteries. For lithium metal, the density is as low as 0.54 g / cm 3 And the standard reduction potential is also very low -3.045 V (SHE: based on standard hydrogen electrode), so it has attracted great attention as an electrode material for high energy density batteries.
[0005] However, unlike conventional lithium-ion secondary batteries, the lithium metal secondary battery is charged while the lithium metal of the negative electrode is plated, and the lithium metal secondary battery is discharged while the lithium metal is stripped, wherein the growth of lithium dendrites occurs during the charging process, thereby causing a short circuit in the battery. And the surface area of the electrode increases, thereby also increasing the side reaction with the electrolyte, so the life characteristics and stability of the battery may deteriorate rapidly. Therefore, in order to commercialize lithium metal electrodes, it is necessary to develop a technology that stabilizes lithium metal electrodes and suppresses dendrites.
[0006] Lithium metal electrodes are usually manufactured by rolling lithium metal strips with rollers. Rollers are mostly made of metal materials to ensure rigidity and durability, and lithium metal has the property of firmly adhering to most metals with just simple contact. Therefore, lubricants must be used in the process of manufacturing lithium metal electrodes to prevent adhesion between the rollers and lithium.
[0007] Japanese Patent Application Publication No. 1998-058007 (Patent Document 1) discloses a method for manufacturing lithium metal foil by using a chain saturated hydrocarbon having more than 8 carbon atoms as a lubricant. However, the problem with the chain saturated hydrocarbon lubricant having more than 8 carbon atoms is that it is difficult to handle due to its high flammability and is very harmful to the human body.
[0008] In addition, Korean Patent Application Publication No. 10-2016-0142350 (Patent Document 2) discloses a method for manufacturing a lithium metal film by using a lubricant composition containing a polymer having a specific structure. However, the lubricant composition also has a problem that an aromatic compound or hydrocarbon having very high flammability and harmful to the human body is used as a solvent. In addition, in the case of using the lubricant composition of Patent Document 2, a passivation layer containing Li2CO3, Li2O and LiOH is formed on the surface of the lithium metal film, wherein there is a limitation in that, due to the uneven plating / stripping of lithium during continuous charging and discharging, the above components continuously react with the electrolyte due to fracture to form dendrites and dead lithium (Li), and cause volume changes. Summary of the invention
[0009] Technical issues
[0010] One aspect of the present invention provides a method for manufacturing a lithium metal electrode, which is harmless to the human body and the environment and can effectively suppress the formation of dendrites due to reaction with an electrolyte by forming a stable protective layer on the surface of the lithium metal electrode.
[0011] Another aspect of the present invention provides a lithium metal secondary battery, wherein the lithium metal secondary battery has excellent resistance characteristics and life characteristics by including the lithium metal electrode manufactured by the above method.
[0012] Technical Solution
[0013] According to one aspect of the present invention, a method for manufacturing a lithium metal electrode is provided, the method comprising the steps of: providing a lithium metal strip; and placing a lubricant composition comprising a fluorine solvent and a fluorine compound on the lithium metal strip, and rolling the lithium metal strip.
[0014] In this case, the fluorine-based solvent may have a boiling point of 150°C or less, preferably 50°C to 130°C, more preferably 80°C to 120°C, and a vapor pressure of 0.1 kPa to 30 kPa, preferably 1 kPa to 20 kPa, more preferably 2 kPa to 10 kPa.
[0015] Specifically, the fluorine-based solvent may be a compound represented by [Formula 1].
[0016] [Formula 1]
[0017] CF3-O-[CF(CF3)-CF2O] x -[CF2O] y -CF3
[0018] In Formula 1, x and y are each independently an integer of 1 to 20.
[0019] The fluorine-based compound may be an oligomer or polymer having a weight average molecular weight of 100 g / mol to 100,000 g / mol (eg, 2,000 g / mol to 20,000 g / mol), and specifically may be an oligomer or polymer including a unit represented by [Formula 2].
[0020] [Formula 2]
[0021] *-[CF2-O] m -[CF2-CF2-O] n -*
[0022] In Formula 2, m and n are each independently an integer of 1 to 100.
[0023] The lubricant composition may include 90 wt % to 99 wt % of the fluorine-based solvent and 1 wt % to 10 wt % of the fluorine-based compound.
[0024] In addition, the lubricant composition may have a viscosity of 0.5 cp to 100 cp.
[0025] According to another aspect of the present invention, there is provided a lithium metal electrode manufactured by the above method, the lithium metal electrode comprising: a lithium metal film; and a protective layer formed on the lithium metal film, wherein the protective layer comprises LiF.
[0026] In this case, LiF may be formed by a reaction between lithium metal and fluorine atoms in the lubricant composition during the rolling step. In addition, the protective layer may include 0.1 wt % to 10 wt % of LiF, and may have a thickness of 0.1 μm to 10 μm.
[0027] According to another aspect of the present invention, a lithium metal battery comprising a positive electrode, a negative electrode and an electrolyte is provided, wherein the lithium metal battery comprises the lithium metal electrode of the present invention as the negative electrode.
[0028] Beneficial Effects
[0029] According to the method for manufacturing a lithium metal electrode of the present invention, lithium reacts with fluorine contained in a lubricant during rolling to form a protective layer containing LiF on the surface of the lithium metal electrode. In the case where a protective layer containing LiF is formed on the surface of the lithium metal electrode, an increase in resistance and a decrease in life characteristics due to a side reaction between lithium metal and an electrolyte can be effectively suppressed.
[0030] Furthermore, the fluorine-based solvent and fluorine-based compound used in the present invention have excellent process stability due to low flammability and toxicity.
[0031] Furthermore, according to the method of manufacturing a lithium metal electrode of the present invention, since the protective layer is formed during the rolling step, a separate coating process is not required to form the protective layer, and thus processability and economic efficiency are excellent.
[0032] Furthermore, since the method of manufacturing a lithium metal electrode of the present invention does not require a separate drying process by using a highly volatile solvent having a boiling point of 150° C. or less and a vapor pressure of 0.1 kPa to 30 kPa as a fluorine-based solvent, processability is excellent.
[0033] Since the lithium metal electrode manufactured according to the method of the present invention includes a protective layer containing LiF on its surface, and unlike components such as Li2CO3, Li2O and LiOH, LiF is not easily decomposed during battery charging and discharging, the lithium metal electrode has an excellent stabilizing effect. Thus, in the case of using the lithium metal electrode manufactured according to the method of the present invention, a lithium metal battery with excellent life characteristics can be manufactured. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 is a view explaining a method of manufacturing a lithium metal electrode according to the present invention;
[0035] Figure 2 is a graph showing the results of measuring life characteristics according to Experimental Example 1;
[0036] Figure 3 is a graph showing the results of evaluating initial resistance characteristics according to Experimental Example 2;
[0037] Figure 4 This is a graph showing the results of evaluating the initial resistance characteristics after 48 hours according to Experimental Example 2. DETAILED DESCRIPTION
[0038] It will be understood that the words or terms used in the specification and claims should not be interpreted as limited to the meanings in commonly used dictionaries, and will also be understood to be interpreted as having meanings consistent with the relevant technical background and technical concepts of the present invention on the basis that the inventor can appropriately define the meanings of the words or terms to interpret the principles of the present invention in the best manner.
[0039] The terms used in this specification are only used to describe exemplary embodiments and are not intended to limit the present invention. Unless otherwise specified, terms in the singular form may include plural forms.
[0040] It will be understood that the terms "include", "comprising" or "having" in this specification are used to clarify the existence of stated features, quantities, steps, elements or a combination thereof, but do not exclude the existence or addition of one or more other features, quantities, steps, elements or a combination thereof.
[0041] Method for manufacturing lithium metal electrodes
[0042] First, a method of manufacturing a lithium metal electrode according to the present invention will be described.
[0043] The method for manufacturing a lithium metal electrode according to the present invention is shown in Figure 1 middle.
[0044] like Figure 1 As shown, the method for manufacturing a lithium metal electrode of the present invention includes the following steps: (1) providing a lithium metal strip 10; and (2) placing a lubricant composition 20 containing a fluorine solvent and a fluorine compound on the lithium metal strip 10, and rolling the lithium metal strip 10.
[0045] The lithium metal strip 10 is a raw material for manufacturing a lithium metal electrode, wherein it is a long strip of lithium metal manufactured by extruding a lithium ingot or rod. The lithium metal strip 10 is provided to a roller press including rollers 30 and passes between the rollers 30 to reduce the thickness of the lithium metal strip, thereby forming a lithium metal film 15.
[0046] The lubricant composition 20 is disposed on the lithium metal strip 10 before the lithium metal strip 10 passes between the rollers 30. In this case, Figure 1 As shown, the lubricant composition 20 can be directly applied to the lithium metal strip 10, or, although not shown, the lubricant composition can be applied to the surface of the roller so that the lubricant composition is disposed on the lithium metal strip when the roller contacts the lithium metal strip.
[0047] In the case of directly applying the lubricant composition 20 onto the lithium metal strip 10 , there is no particular limitation on the coating method, and various coating methods known in the art, for example, methods such as spraying, bar coating, or dip coating may be used.
[0048] If rolling is performed after the lubricant composition 20 is provided as described above, the lithium metal strip 10 is rolled to form the lithium metal film 15, and a thin polymer layer is formed on the surface of the lithium metal film 15 by the fluorine compound contained in the lubricant composition to prevent the lithium metal strip 10 from adhering to the roller 30. In addition, the fluorine atoms contained in the lubricant composition react with the lithium metal by rolling to form LiF, thereby manufacturing a lithium metal electrode having the lithium metal film 15 and the protective layer 25 formed on the surface of the lithium metal film 15 and containing LiF.
[0049] The lubricant composition used in the present invention contains a fluorine-based solvent and a fluorine-based compound.
[0050] Since the fluorine-based solvent has excellent compatibility with the fluorine-based compound described later, it dissolves the fluorine-based compound well, so that the lubricant composition can be smoothly applied to the lithium metal ribbon.
[0051] It is desirable that the fluorine-based solvent has a boiling point of 150°C or lower, preferably 50°C to 130°C, more preferably 80°C to 120°C.
[0052] In addition, it is desirable that the fluorine-based solvent is a solvent having a vapor pressure of 0.1 kPa to 30 kPa, preferably 1 kPa to 20 kPa, and more preferably 2 kPa to 10 kPa.
[0053] When the boiling point and vapor pressure of the fluorine-based solvent meet the above ranges, the fluorine-based solvent is easily volatilized at room temperature, so there is no need to remove the solvent through a separate drying process. Specifically, the fluorine-based solvent may be a compound represented by [Formula 1].
[0054] [Formula 1]
[0055] CF3-O-[CF(CF3)-CF2O] x -[CF2O] y -CF3
[0056] In Formula 1, x and y may be an integer of 1 to 20, preferably an integer of 1 to 8, and more preferably an integer of 1 to 4, each independently.
[0057] Next, the fluorine-based compound prevents adhesion between the roller and the lithium metal ribbon by forming a thin polymer layer on the surface of the lithium metal ribbon.
[0058] In the present invention, the fluorine compound contains fluorine atoms and may be an oligomer or polymer having a weight average molecular weight (Mw) of 100 g / mol to 100,000 g / mol, preferably 2,000 g / mol to 20,000 g / mol, and more preferably 5,000 g / mol to 10,000 g / mol. If the weight average molecular weight of the fluorine compound is too small, the lubrication performance is poor because the polymer layer cannot be smoothly formed on the lithium metal strip, and if the weight average molecular weight is too large, the viscosity of the lubricant composition may increase, so it may not be sprayed or coated on the lithium metal strip smoothly.
[0059] More specifically, the fluorine-based compound may be an oligomer or a polymer including a unit represented by the following [Formula 2].
[0060] [Formula 2]
[0061] *-[CF2-O] m -[CF2-CF2-O] n -*
[0062] In Formula 2, m and n may each independently be an integer of 1 to 100, preferably an integer of 20 to 80, and more preferably an integer of 40 to 60.
[0063] The lubricant composition may include the fluorine-based solvent in an amount of 90 wt % to 99 wt %, preferably 95 wt % to 99 wt %, and more preferably 96 wt % to 98 wt %.
[0064] Furthermore, the lubricant composition may include the fluorine-based compound in an amount of 1 wt % to 10 wt %, preferably 1 wt % to 5 wt %, and more preferably 2 wt % to 4 wt %.
[0065] If the amount of the fluorine compound in the lubricant composition is too low, the lubrication performance is poor because the polymer layer cannot be smoothly formed on the lithium metal strip, and if the amount is too large, the fluorine compound may not be dissolved in the fluorine solvent or the viscosity of the lubricant composition may increase, so it may not be sprayed or coated smoothly on the lithium metal strip.
[0066] In addition, the lubricant composition may have a viscosity of 0.5 to 100 cp, preferably 1 to 20 cp, and more preferably 1 to 5 cp, measured at 20° C. In the case where the viscosity of the lubricant composition satisfies the above range, the lubricant composition is smoothly sprayed and has excellent lubrication performance.
[0067] The lithium metal electrode of the present invention manufactured by the above method comprises a lithium metal film and a protective layer formed on the surface of the lithium metal film and containing LiF. Because LiF, which is different from components such as Li2CO3, Li2O and LiOH, is not easily decomposed during battery charging and discharging, by stably coating the surface of the lithium metal electrode, the contact between the lithium metal electrode and the electrolyte can be effectively prevented even during repeated charging and discharging, thereby effectively inhibiting the formation of lithium dendrites caused by side reactions with the electrolyte. Thus, if the lithium metal electrode manufactured according to the method of the present invention is used, the life characteristics of the lithium metal battery can be improved.
[0068] Lithium Metal Batteries
[0069] Next, a lithium metal battery according to the present invention will be described.
[0070] The lithium metal battery according to the present invention comprises a lithium metal electrode manufactured according to the above method. Specifically, the lithium metal battery according to the present invention comprises a positive electrode, a negative electrode and an electrolyte, and may comprise a lithium metal film and a protective layer formed on the surface of the lithium metal film and containing LiF as a negative electrode. In addition, if necessary, the lithium metal battery according to the present invention may also comprise a separator.
[0071] The lithium metal battery of the present invention may be, for example, a lithium-sulfur battery. Preferably, the lithium metal battery of the present invention may be a lithium-sulfur battery capable of achieving high capacity characteristics.
[0072] Hereinafter, each component of the lithium metal battery of the present invention will be described in more detail.
[0073] negative electrode
[0074] The negative electrode is a lithium metal electrode manufactured according to the method of the present invention, wherein it comprises a lithium metal film and a protective layer formed on the surface of the lithium metal film.
[0075] The protective layer contains a LiF component formed by a reaction between lithium metal and fluorine atoms in the lubricant composition during the rolling step. The protective layer containing LiF does not decompose even during repeated charging and discharging, and stably coats the surface of the lithium metal electrode, thereby effectively preventing contact between the lithium metal electrode and the electrolyte.
[0076] The protective layer may contain 0.1 wt % to 10 wt %, preferably 0.5 wt % to 5 wt %, more preferably 1 wt % to 2 wt % LiF based on the total weight of the protective layer. When the amount of LiF in the protective film satisfies the above range, the side reaction with the electrolyte can be effectively blocked while ensuring lithium ion conductivity.
[0077] The thickness of the protective layer may be 0.1 μm to 10 μm, preferably 0.5 μm to 5 μm, and more preferably 1 μm to 3 μm. When the thickness of the protective layer satisfies the above range, the side reaction with the electrolyte can be effectively blocked while ensuring lithium ion conductivity.
[0078] positive electrode
[0079] As the positive electrode, various positive electrodes used in lithium metal batteries can be used. For example, the positive electrode may have a form in which a positive electrode active material layer is stacked on a positive electrode current collector.
[0080] As the positive electrode active material, a common positive electrode active material used in a lithium metal battery may be used, for example, a sulfur-containing compound may be used.
[0081] As the sulfur-containing compound, for example, at least one selected from the following can be used: Li2S n (n=1); disulfide compounds such as 2,5-dimercapto-1,3,4-thiadiazole and 1,3,5-trimerthiocyanate; organic sulfur compounds; and carbon-sulfur complexes may be used.
[0082] If necessary, a conductive material or a binder may be further contained in the positive electrode active material layer.
[0083] The conductive material not only provides electronic conductivity by serving as a path for electrons to move from the current collector to the positive electrode active material, but also serves as a transport medium for lithium ions (Li ions) dissolved in the electrolyte. + ) moves to sulfur and reacts by electrically connecting the electrolyte and the positive electrode active material.
[0084] There is no particular limitation on the conductive material as long as it has conductivity without causing adverse chemical changes in the battery, and conductive materials such as graphite, carbon black such as Deko Black, acetylene black, Ketjen Black, channel black, furnace black, lamp black, and thermal black, conductive fibers such as carbon fibers or metal fibers, fluorocarbons, metal powders such as aluminum powder and nickel powder, conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers, conductive metal oxides such as titanium oxide, or polyphenylene derivatives can be used. As specific examples of commercial conductive materials, acetylene black products (Chevron Chemical Company, Denka Singapore Private Limited, or Gulf Oil Company), Ketjen Black, ethylene carbonate (EC) products (Armak Company), Vulcan XC-72 (Cabot Company), and Super P (Timcal Graphite & Carbon) can be used.
[0085] The binder is a component that facilitates the bonding between the active material and the conductive material and the bonding with the collector, wherein the binder suitable for the present invention may be all binders known in the art, and, specifically, the binder may be at least one selected from the following or a mixture or copolymer of two or more thereof: fluororesin binders, including polyvinylidene fluoride (PVDF) or polytetrafluoroethylene (PTFE); rubber binders, including styrene-butadiene rubber, nitrile rubber or styrene-isoprene rubber; cellulose binders, including carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose or regenerated cellulose; polyol binders; polyolefin binders, including polyethylene or polypropylene; polyimide binders; polyester binders; and silane binders, but not limited thereto.
[0086] Electrolytes
[0087] As the electrolyte, a liquid electrolyte, an organic solid electrolyte, and an inorganic solid electrolyte used in a secondary battery can be used, and the type thereof is not particularly limited.
[0088] For example, the liquid electrolyte may include an organic solvent and a lithium salt.
[0089] Any organic solvent can be used as the organic solvent without particular limitation, as long as it can act as a medium through which ions participating in the electrochemical reaction of the battery can move. Specifically, as the organic solvent, ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone and ε-caprolactone can be used; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (PC); alcohol solvents such as ethanol and isopropanol; nitrile such as Ra-CN (wherein Ra is a straight chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, and may contain a double bond, an aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolanes; or cyclopentane sulfone.
[0090] Lithium salts can be used without particular limitation as long as they are compounds that can provide lithium ions for lithium secondary batteries. Specifically, as lithium salts, LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI or LiB(C2O4)2 can be used. The lithium salt can be used in a concentration range of 0.1M to 2.0M. If the concentration of the lithium salt is included in the above range, since the electrolyte can have appropriate conductivity and viscosity, the excellent performance of the electrolyte can be obtained and the lithium ions can be effectively moved.
[0091] In order to improve the life characteristics of the battery, inhibit the reduction of the battery capacity, and increase the discharge capacity of the battery, in addition to the above-mentioned electrolyte components, the electrolyte may also contain at least one additive, for example: halogenated alkylene carbonate compounds, such as difluoroethylene carbonate; pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, (condensed) glycol dimethyl ether, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum trichloride. In this case, the content of the additive may be 0.1 wt % to 10 wt % based on the total weight of the electrolyte.
[0092] As the organic solid electrolyte, for example, polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate polymers, polyalginate-lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, and polymers containing ion dissociative groups can be used.
[0093] As an inorganic solid electrolyte, for example, a nitride, halide or sulfate of lithium (Li) such as Li3N, LiI, Li5NI2, Li3N-LiI-LiOH, LiSiO4, LiSiO4-LiI-LiOH, Li2SiS3, Li4SiO4, Li4SiO4-LiI-LiOH and Li3PO4-Li2S-SiS2 can be used.
[0094] Diaphragm
[0095] The separator separates the negative electrode and the positive electrode and provides a movement path for lithium ions, wherein any separator can be used as the separator without particular limitation as long as it is commonly used as a separator in secondary batteries, and in particular, a separator having high moisture retention capacity for electrolytes and low resistance to electrolyte ion migration can be used.
[0096] Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer and ethylene / methacrylate copolymer; or a laminated structure having two or more layers thereof can be used.
[0097] Furthermore, a typical porous nonwoven fabric, for example, a nonwoven fabric formed of high-melting-point glass fiber or polyethylene terephthalate fiber may be used.
[0098] Furthermore, a coated separator including a ceramic component or a polymer material may be used to ensure heat resistance or mechanical strength, and a separator having a single-layer or multi-layer structure may be optionally used.
[0099] The lithium metal battery as described above can be suitably used in: portable devices such as mobile phones, notebook computers, and digital cameras; and electric vehicles such as hybrid electric vehicles (HEVs).
[0100] In addition, the lithium metal battery according to the present invention can be used as a unit cell of a battery module, and the battery module can be used in a battery pack. The battery module or battery pack can be used as a power source for at least one of the following medium and large devices: power tools; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles, and plug-in hybrid electric vehicles (PHEVs); or power storage systems.
[0101] Example
[0102] Hereinafter, the present invention will be described in detail according to specific examples. However, the present invention can be embodied in many different forms and should not be construed as being limited to the embodiments set forth herein. On the contrary, these exemplary embodiments are provided to make this specification detailed and complete and to fully convey the scope of the present invention to those skilled in the art.
[0103] Example 1
[0104] By mixing a fluorine-based solvent CF3-O-[CF(CF3)-CF2O]2-CF2O-CF3 (boiling point 105°C, vapor pressure: 2.5 kPa) with a fluorine-based compound Z15 (manufacturer: Solvay, weight average molecular weight of 8,000 g / mol) was mixed at a weight ratio of 97.6:2.4 to prepare a lubricant composition. The viscosity of the prepared lubricant composition was measured at 20° C. using a Brookfield viscometer (model name: DV2TLV), and the measured viscosity was 1.2 cp.
[0105] A 60 μm thick lithium metal strip was provided to a roller press, and after the lubricant composition was applied to the lithium metal strip, the lithium metal strip was rolled with a roller to produce a 45 μm thick lithium metal electrode.
[0106] Example 2
[0107] By mixing a fluorine-based solvent CF3-O-[CF(CF3)-CF2O]2-CF2O-CF3 (boiling point 105°C, vapor pressure: 2.5 kPa) with a fluorine-based compound Z15 (manufacturer: Solvay, weight average molecular weight 8,000 g / mol) was mixed at a weight ratio of 96:4 to prepare a lubricant composition. The viscosity of the prepared lubricant composition was measured at 20° C. using a Brookfield viscometer (model name: DV2TLV), and the measured viscosity was 1.5 cp.
[0108] A 60 μm thick lithium metal strip was provided to a roller press, and after the lubricant composition was applied to the lithium metal strip, the lithium metal strip was rolled with a roller to produce a 45 μm thick lithium metal electrode.
[0109] Example 3
[0110] By mixing a fluorine-based solvent CF3-O-[CF(CF3)-CF2O]2-CF2O-CF3 (boiling point 105°C, vapor pressure: 2.5 kPa) with a fluorine-based compound Z25 (manufacturer: Solvay, weight average molecular weight 9,500 g / mol) was mixed at a weight ratio of 97.6:2.4 to prepare a lubricant composition. The viscosity of the prepared lubricant composition was measured at 20° C. using a Brookfield viscometer (model name: DV2TLV), and the measured viscosity was 1.4 cp.
[0111] A 60 μm thick lithium metal strip was provided to a roller press, and after the lubricant composition was applied to the lithium metal strip, the lithium metal strip was rolled with a roller to produce a 45 μm thick lithium metal electrode.
[0112] Comparative Example 1
[0113] A lithium metal electrode was manufactured in the same manner as in Example 1, except that octane (a chain saturated hydrocarbon having 8 carbon atoms) was used as a lubricant instead of the lubricant composition of Example 1.
[0114] Experimental Example 1
[0115] <Manufacturing of positive electrode>
[0116] A positive electrode slurry composition was prepared by mixing a mixture of 90 parts by weight of a sulfur-carbon composite (weight ratio of S:C = 7:3) as a positive electrode active material, 5 parts by weight of Deko Black as a conductive material, and 5 parts by weight of a binder, in which styrene-butadiene rubber and carboxymethyl cellulose were mixed in a weight ratio of 7:3.
[0117] Then, an aluminum current collector was coated with the prepared positive electrode slurry composition, dried at 50° C. for 12 hours, and then roll-pressed to manufacture a positive electrode. The manufactured positive electrode had a capacity of 5.4 mAh / cm 2 of loading and a porosity of 68%.
[0118] The positive electrode manufactured as described above, a polyethylene separator (thickness: 20 μm, porosity: 68%), and various lithium metal electrodes manufactured in Examples 1 to 3 and Comparative Example 1 were stacked in order, and 0.1 ml of the electrolyte was injected to manufacture a lithium-sulfur battery.
[0119] In this case, as an electrolyte, a mixed solution was used in which 1 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 1 wt % lithium nitrate (LiNO 3 ) were dissolved in a mixed organic solvent containing 1,3-dioxolane and dimethyl ether at a volume ratio of 1:1.
[0120] After the lithium-sulfur battery manufactured as described above was charged and discharged 3 times at a current density of 0.1C at 25°C and then discharged and charged 3 times at a current density of 0.2C, the life characteristics of the battery were evaluated by measuring the discharge capacity and coulombic efficiency while the battery was discharged at 0.5C and charged at 0.3C. The measurement results are shown in Figure 2 middle.
[0121] like Figure 2As shown, for the lithium-sulfur battery including the lithium metal electrode of Comparative Example 1, the discharge capacity and coulombic efficiency rapidly decreased after 80 cycles, but for the lithium-sulfur batteries including the lithium metal electrodes of Examples 1 to 3 respectively manufactured by the method of the present invention, it can be confirmed that the discharge capacity and coulombic efficiency remain excellent.
[0122] Experimental Example 2
[0123] A symmetric cell having a lithium metal electrode / separator / lithium metal electrode structure was manufactured by using the various lithium metal electrodes manufactured in Examples 1 to 3 and Comparative Example 1, and 0.1 ml of the electrolyte was injected.
[0124] In this case, as an electrolyte, a mixed solution was used in which 1 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 1 wt % lithium nitrate (LiNO 3 ) were dissolved in a mixed organic solvent containing 1,3-dioxolane and dimethyl ether at a volume ratio of 1:1.
[0125] Electrochemical impedance spectroscopy (EIS) analysis was performed on various symmetrical cells manufactured as described above to measure the initial resistance characteristics just after the cells were manufactured and the resistance characteristics after 48 hours. The measurement amplitude was 5 mV and the frequency range was 0.1 Hz to 1 MHz. The initial resistance characteristics measurement results are shown in Figure 3 The resistance characteristics after 48 hours are shown in Figure 4 middle.
[0126] refer to Figure 3 and Figure 4 In the case of the lithium metal electrodes of Examples 1 to 3 manufactured by the method of the present invention, it can be confirmed that the initial resistance characteristics and the resistance characteristics after 48 hours are better than the case of the lithium metal electrode of Comparative Example 1.
[0127] <Reference Numbers>
[0128] 10: Lithium metal belt
[0129] 15: Lithium metal film
[0130] 20: Lubricant composition
[0131] 25: Protective layer
[0132] 30: Roller
Claims
1. A method for manufacturing a lithium metal electrode, the method comprising the following steps: providing lithium metal strips; and placing a lubricant composition containing a fluorine-based solvent and a fluorine-based compound on the lithium metal strip, and rolling the lithium metal strip, The fluorine-based solvent is a compound represented by Formula 1, [Formula 1] CF3-O-[CF(CF3)-CF2O] x -[CF2O] y -CF3 in, In Formula 1, x and y are each independently an integer from 1 to 20, wherein the fluorine-based compound comprises a unit represented by Formula 2, [Formula 2] *-[CF2-O] m -[CF2-CF2-O] n -* In Formula 2, m and n are each independently an integer of 1 to 100. 2 . The method according to claim 1 , wherein the fluorine-based solvent has a boiling point of 150° C. or less and a vapor pressure of 0.1 kPa to 30 kPa. 3 . The method according to claim 1 , wherein the fluorine-based solvent has a boiling point of 50° C. to 130° C. and a vapor pressure of 1 kPa to 20 kPa. 4 . The method according to claim 1 , wherein the fluorine-based solvent has a boiling point of 80° C. to 120° C. and a vapor pressure of 2 kPa to 10 kPa. The method according to claim 1 , wherein the fluorine-based compound has a weight average molecular weight of 100 g / mol to 100,000 g / mol. The method according to claim 1 , wherein the fluorine-based compound has a weight average molecular weight of 2,000 g / mol to 20,000 g / mol. 7 . The method according to claim 1 , wherein the lubricant composition comprises 90 wt % to 99 wt % of the fluorine-based solvent and 1 wt % to 10 wt % of the fluorine-based compound.
8. The method of claim 1, wherein the lubricant composition has a viscosity of 0.5 cp to 100 cp.
9. A lithium metal electrode, the lithium metal electrode being manufactured by the method according to any one of claims 1 to 8, and The lithium metal electrode comprises: a lithium metal film; and a protective layer formed on the lithium metal film, The protective layer comprises LiF.
10. The lithium metal electrode of claim 9, wherein the LiF is formed during the rolling step by a reaction between lithium metal and fluorine atoms in the lubricant composition.
11. The lithium metal electrode of claim 9, wherein the protective layer comprises 0.1 wt% to 10 wt% LiF. 12 . The lithium metal electrode according to claim 9 , wherein the protective layer has a thickness of 0.1 μm to 10 μm.
13. A lithium metal battery, comprising a positive electrode, a negative electrode and an electrolyte, The negative electrode is the lithium metal electrode according to claim 9. 14 . The lithium metal battery according to claim 13 , wherein the positive electrode comprises a positive electrode active material comprising at least one selected from the group consisting of a metal oxide and a sulfur compound.
15. The lithium metal battery according to claim 13, wherein the lithium metal battery is a lithium-sulfur battery.
Citation Information
Patent Citations
Manufacture of lithium metal foil or lithium alloy foil
JP1998058007A
Polymers and the use thereof as lubricating agents in the production of alkali metal films
KR1020160142350A
Apparatus for processing substrate and method of control using the same
KR1020200072106A
Method for forming lithium metal positive-pole protective layer of lithium cell
CN1389940A
Coating fluid and method of forming coating film
WO2007086384A1